2010
DOI: 10.1007/s00247-010-1897-y
|View full text |Cite
|
Sign up to set email alerts
|

Differences in MRI findings between subgroups of recent-onset childhood arthritis

Abstract: BackgroundMRI is sensitive for joint inflammation, but its ability to separate subgroups of arthritis in children has been questioned. Infectious arthritis (IA), postinfectious arthritis (PA), transient arthritis (TA) and juvenile idiopathic arthritis (JIA) are subgroups that may need early, different treatment.ObjectiveTo determine whether MRI findings differ in IA, PA/TA and JIA in recent-onset childhood arthritis.Materials and methodsFifty-nine children from a prospective study of incidence of arthritis (n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 23 publications
1
14
0
2
Order By: Relevance
“…In the current study, we showed that MRI might be helpful in aiding the differentiation JIA from other causes of knee pain/symptoms in clinically suspected non-infectious arthritis. Our results are in line with another study assessing differences in MRI findings between subgroups of recent-onset childhood arthritis [ 24 ], and supports the notion that physical examination could be supported by more sensitive tools such as MRI.…”
Section: Discussionsupporting
confidence: 91%
“…In the current study, we showed that MRI might be helpful in aiding the differentiation JIA from other causes of knee pain/symptoms in clinically suspected non-infectious arthritis. Our results are in line with another study assessing differences in MRI findings between subgroups of recent-onset childhood arthritis [ 24 ], and supports the notion that physical examination could be supported by more sensitive tools such as MRI.…”
Section: Discussionsupporting
confidence: 91%
“…While osteopenia was the most common finding, joint space narrowing and erosions were also observed [22,23]. Other studies using MRI demonstrated irregular synovial thickening and low-intensity synovial tissue, not only in recent-onset JIA, but also in joints prior to the onset of clinical symptoms [24,25]. In addition, localized growth disturbances have been reported in 10-48% of children within the first 2-3 years after diagnosis [16,22].…”
Section: Discussionmentioning
confidence: 97%
“…Kirkhus et al found nonenhancing low signal intensity synovial tissue and irregular thickness of the synovium to be more frequent in JIA than in infectious arthritis. 24 Nistala et al found that the erythrocyte sedimentation rate (ESR) was predictive of active hip arthritis on MRI. 11 They showed that a highly elevated ESR is specific for hip inflammation, but that hip arthritis on MRI may be present with a normal ESR.…”
Section: Juvenile Idiopathic Arthritismentioning
confidence: 99%